Job Displacement and First Birth over the Business Cycle - Barbara Hofmann; Michaela Kreyenfeld; Arne Uhlendorff (Institute of Labor Economics (IZA), 2017)
This paper investigates the impact of job displacement on women's first birth rates, and the variation in this effect over the business cycle. We used mass layoffs to estimate the causal effects of involuntary job loss on fertility in the short and medium term, up to five years after displacement. Our analysis is based on rich administrative data from Germany, with an observation period spanning more than 20 years. We apply inverse probability weighting (IPW) to flexibly control for the observed differences between women who were and were not displaced. To account for the differences in the composition of the women who were displaced in a downturn and the women who were displaced in an upswing, a double weighting estimator was employed. We find that the extent to which job displacement had adverse effects on fertility depended on the business cycle. The first birth rates of the women who were displaced in an economic downturn were much lower than the first birth rates of the women who lost a job in an economic upturn. This result cannot be explained by changes in the observed characteristics of the displaced women over the business cycle.
Keywords: J13; J64; J65; 330; fertility; job loss; mass layoffs; business cycle; unemployment